The nucleation of receptor-mediated endocytosis. - Edwards, D A (1996)
A theory of the mechanical origins of receptor-mediated endocytosis shows that a spontaneous membrane complex formation can provide the stimulus for a local membrane motion toward the cytosol. This motion is identified with a nucleation stage of receptor-mediated endocytosis. When membrane complexes cluster, membrane deformation is predicted to be most rapid. The rate of growth of membrane depressions depends upon the relative rates of approach of aqueous cytosolic and extracellular fluids toward the cell membrane. With cytosolic and extracellular media characterized by apparent viscosities, the rate of growth of membrane depressions is predicted to increase as the extracellular viscosity nears the apparent viscosity of the cytosol and then to decrease when the extracellular viscosity exceeds that of the cytosol. To determine whether these trends would be apparent in the overall endocytosis rate constant, an experimental study of transferrin-mediated endocytosis in two different cell lines was conducted. The experimental results reveal the same dependence of internalization rate on extracellular viscosity as predicted by the theory. These and other comparisons with experimental data suggest that the nucleation stage of receptor-mediated endocytosis is important in the overall endocytosis process.